Implementasi Kurikulum MBKM Terhadap Minat dan Hasil Belajar - Saepul Mustakim, Usep (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Babunnajah Pandeglang, 2024)
Teaching and learning activities are expected to be carried out well with optimal learning outcomes. The purpose of this study was to find out how effective learning activities are in implementing the